2009
DOI: 10.1109/tip.2008.2009796
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Evaluation of Spatial Resolution and Quantization Noise Tradeoffs

Abstract: Abstract-Most full-reference fidelity/quality metrics compare the original image to a distorted image at the same resolution assuming a fixed viewing condition. However, in many applications, such as video streaming, due to the diversity of channel capacities and display devices, the viewing distance and the spatiotemporal resolution of the displayed signal may be adapted in order to optimize the perceived signal quality. For example, at low bitrate coding applications an observer may prefer to reduce the reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The relationship between quantization distortion and display resolution was studied through subjective tests conducted by Bae et al [14]. Using the quantization distortion of JPEG and JPEG2000, they showed that users accept more compression artifacts when the display resolution is lower.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between quantization distortion and display resolution was studied through subjective tests conducted by Bae et al [14]. Using the quantization distortion of JPEG and JPEG2000, they showed that users accept more compression artifacts when the display resolution is lower.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the tradeoff between resolution/viewing conditions and visibility of compression artifacts, a subjective evaluation experiment is conducted in [16], where 4 images are compressed using JPEG and JPEG2000 at different bit rates. Another subjective study conducted in [17] tries to measure the quality of distorted image with a lower resolution compared to the reference image.…”
Section: Introductionmentioning
confidence: 99%